(untitled) (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2013)
The research presented ’s main purpose is to design a system of performance indicators for the public sector : HIDROANDES , CA , if a non- experimental research performed with support from a field study , descriptive and documentary , practiced a diagnosis the strategic management of the company to respond to the problem. Were analyzed and recorded the events that occurred in the department studied. The study unit was composed of the most important managers of the company, which was consulted on 23 subjects of information, to which was applied a questionnaire as a data collection instrument. The instrument was structured with open and closed questions. Core processes and subsequently, the areas and critical activity of each process are identified. Variables were identified to be controlled and a total of 76 profiles of indicators that make up the model proposed performance indicators for the company under study , with which we can evaluate the efficiency and effectiveness criteria are designed.